2014
DOI: 10.9790/2380-07119395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Aloe vera and Yeast powder on muscle growth of broiler chicks

Abstract: The purpose of this research work was to evaluate the Aloe vera (Aloe barbadensis) and Yeast (Saccharomyces Cerevisiae)powder. A total of 72 (Arbor-Acres) day old chicks were used in this study. Four levels of anAloe vera and Yeast powder at the rate of 0.00%, 0.50% (Yeast), 0.50% (Aloe vera), and 0.50% Yeast + 0.50% Aloe vera were incorporated into the basal diet for six weeks. Feeding period for all groups was lasted for 42 days. Results revealed a significant effect of Aloe vera and Yeast powder in feeds on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…It is similar to Doley et al . [ 18 ] who found increased (p<0.05) weight of breast, thigh, and leg in groups supplemented with 0.5% Yeast and A. vera as compared to control group. Increased breast weight was also found in broilers supplemented with clove and cinnamon [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is similar to Doley et al . [ 18 ] who found increased (p<0.05) weight of breast, thigh, and leg in groups supplemented with 0.5% Yeast and A. vera as compared to control group. Increased breast weight was also found in broilers supplemented with clove and cinnamon [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mansoub (2011) observed that herbal plants enhance carcass quality through effective nutrient utilization, higher and efficient absorption of amino acids which enhances protein metabolism and muscle deposition in birds. Doleyi et al (2014); Tariq et al (2015) reported significant increase in thigh and breast weights of birds fed fennel seed powder at 450g/100kg.…”
Section: Carcass Characteristics Of Broiler Birds Fed Varying Level O...mentioning
confidence: 97%